A note on the usage of Likert Scaling for research data analysis - Pimentel, Jonald L. (2010)
In this paper, biases on some used known method adapting Likert Scaling are shown. Then, an improvement of the method to correct or minimize the bias is presented in order to have better interpretation of the result of the analysis of the data
Keywords: Likert Scale; Psychometric scale